A prática pedagógica em ciências e a formação cidadã: experiência freiriana da Escola Zandoná - Barra Funda/RS - Rochembach, Eduarda Souza (2023)
The present dissertation is inserted in the research line "Educational Processes and Language" of the Graduate Program in Education at the University of Passo Fundo. The study addresses the issue of the relationship between theory and practice based on a reality in which, on the one hand, teachers encounter theoretical frameworks guiding pedagogical practices assumed by the school or educational network to which they are linked, and on the other hand, with their practices established throughout their formative and professional process, permeated by their beliefs and choices regarding teaching and learning. From this identification, the research takes as its focus a case study associated with a public school that follows a pedagogical proposal based on the Freirean perspective of education, involving citizenship education. Its focus is to analyze how these assumptions are present when teachers address Natural Sciences content. The central question of the investigation is structured around the following question: considering a Freirean pedagogical orientation curriculum, how does citizenship education manifest in the didactic actions developed by teachers who teach Natural Sciences? The objective is to investigate how teachers who teach Natural Sciences classes incorporate citizenship education within a Freirean conception, adhering to the theoretical assumptions present in the curriculum of the State School of Basic Education Antônio João Zandoná, in Barra Funda, RS. To achieve this, support is sought in discussions about education and citizenship formation from the perspective of Paulo Freire, incorporating recent research on the topic, especially in the context of Science Education. Methodologically, the study is characterized as qualitative, descriptive, and linked to a case study, using a questionnaire and semi-structured interviews as instruments for data production. The participants are six teachers and two pedagogical coordinators, numbers defined by saturation. Content Analysis, based on Laurence Bardin's perspective (2020), is the methodology for data analysis, using categories established a posteriori and resulting from the participants' statements. As a result, it is identified that the school's organizational proposal is not ready-made or finished, nor a recipe to be followed, but something that is constituted and reformulated daily, entirely dependent on the engagement of the entire collective. It is observed in the school that citizenship education is present in the didactic actions of Natural Sciences teachers when it allows connecting scientific concepts to social issues and stimulates the students' critical thinking for conscious decision-making. However, the school organization faces numerous challenges, notably the introduction of new concepts focused on the job market at the expense of educational principles, as well as community resistance due to disagreements with the methodological principles of the proposal